2017
DOI: 10.1111/pbi.12709
|View full text |Cite
|
Sign up to set email alerts
|

Next‐generation transgenic cotton: pyramiding RNAi and Bt counters insect resistance

Abstract: SummaryTransgenic crops producing insecticidal proteins from the bacterium Bacillus thuringiensis (Bt) are extensively cultivated worldwide. To counter rapidly increasing pest resistance to crops that produce single Bt toxins, transgenic plant ‘pyramids’ producing two or more Bt toxins that kill the same pest have been widely adopted. However, cross‐resistance and antagonism between Bt toxins limit the sustainability of this approach. Here we describe development and testing of the first pyramids of cotton com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 53 publications
8
77
0
4
Order By: Relevance
“…A similar phenotype has been described for Tribolium castaneum larvae microinjected with dsRNA of the JH‐inducible Krüppel homolog‐1 gene; the larvae displayed remains of the old tegument attached to the body, undergoing an early metamorphosis to the pupae stage . Silencing another gene linked to JH metabolism, juvenile hormone‐binding protein, by feeding H. armigera on RNAi cotton plants increased larval mortality . Although silencing of JHP has not been previously reported in lepidopterans, our results with T. absoluta indicate that targeting this gene might be effective and promising in an RNAi control strategy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A similar phenotype has been described for Tribolium castaneum larvae microinjected with dsRNA of the JH‐inducible Krüppel homolog‐1 gene; the larvae displayed remains of the old tegument attached to the body, undergoing an early metamorphosis to the pupae stage . Silencing another gene linked to JH metabolism, juvenile hormone‐binding protein, by feeding H. armigera on RNAi cotton plants increased larval mortality . Although silencing of JHP has not been previously reported in lepidopterans, our results with T. absoluta indicate that targeting this gene might be effective and promising in an RNAi control strategy.…”
Section: Discussionsupporting
confidence: 85%
“…One example is the use of a plant pyramidal transformation to express dsRNA of CHI and JHP or a mixture of bacteria expressing both genes (together or as a mixture of bacteria solution). Helicoverpa armigera fed on cotton plants expressing proteins Cry and dsRNA of juvenile hormone acid methyltransferase and juvenile hormone binding protein genes showed higher mortality when compared with larvae fed on plants with just one transgenic event …”
Section: Discussionmentioning
confidence: 99%
“…The principle of plant‐mediated RNAi is that it can silence the expression of key developmental or reproductive genes using exogenous dsRNA, which causes pest developmental stagnation or a direct lethal effect, finally achieving the purpose of controlling the target pest population. When an insect eats such transgenic plants, expression of the target gene can be significantly reduced, and this can function as a form of long‐lasting inhibition of pest growth . In recent years, important progress has been made in pest control strategies based on RNAi .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, for example, studies demonstrated a high efficiency of the Bt soybean strain DAS-81419-2 (expressing two proteins) in the reduction of damage caused by A. gemmatalis, C. includens, H. virescens, and S. cosmioides during the vegetative and reproductive stages (Marques et al 2016). Recent studies have suggested the use of RNA interference as a promising alternative or complementary strategy for pest control and management (Asokan et al 2014;Kim et al 2015;Fishilevich et al 2016;Yu et al 2016;Ni et al 2017). …”
Section: Management Of Resistancementioning
confidence: 99%
“…The technological solution to this problem is the production of transgenic plants expressing a higher number of Bt toxins, as indicated in the results obtained by Marques et al (2017), which show the high efficiency of a soybean variety containing two Bt toxins in the control of primary and secondary pests. The recommended strategies for controlling problematic pests are the cultivation of plants expressing genes for two or three Bt toxins, the expansion of refuge areas, and the use of other management tactics (Carrière et al 2016a(Carrière et al , 2016bNi et al 2017). …”
Section: Final Considerationsmentioning
confidence: 99%